A rare case of pontine tegmental cap dysplasia - Mosab Maree, MD; Islam Rajab, MD; Andrew Edward Leung, MD; Keng Yeow Tay, MD; Shivaprakash B. Hiremath, MD (Radiology Case Reports)
Pontine Tegmental Cap Dysplasia (PTCD) is a rare hindbrain malformation characterized by cranial nerve dysfunction, cerebellar abnormalities, and developmental delays of varying severity. This case report presents a 12-month-old female with significant developmental delays, hypotonia, and cranial nerve abnormalities. The findings underscore the critical role of radiology and neuroimaging in diagnosing and managing PTCD. Additionally, this case highlights the importance of neuroimaging in differentiating PTCD from other possible diagnoses and malformations